STUDI TENTANG NILAI-NILAI MORAL DALAM TRADISI REBO WEKASAN DI DESA SUNGAICINA KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Siti Nurjannah; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the Rebo Wekasan tradition of theJavanese Tribe community. This tradition has been going on for a long time, carried outby the Javanese people. With the development of an increasingly advanced era of theWekasan Rebo tradition, there are a series of activities that are no longer carried out,such as eating diamonds and bathing on the safar, thereby diminishing the moral valuesthat exist in this Wekasan Rebo tradition. The purpose of this study was to find out howthe implementation and moral values in the Rebo Wekasan tradition in the Javanesepeople in Sungaicina Village, Rangsang Barat District, Meranti Islands Regency. Theresearch method uses descriptive qualitative methods and data collection techniques inthis study are Observation, Interview and Documentation. The informants in this studyused the snowball sampling technique so that as many as 7 people were collected,namely religious scholars, families who carry out the Rebo Wekasan tradition, villageyouth and local communities. Based on the results of the study, it can be concluded thatthe implementation of the Rebo Wekasan tradition starts from praying, recitation,reading the prayer to reject reinforcements, taking water from the well and visiting thegrave. kinship such as praying together with a prayer to reject reinforcements in thehope that safety is given to all who carry out the Rebo Wekasan tradition, the moralvalue of friendship such as gathering in a place so that friendship is established and themoral value of harmony such as the existence of community, namely by bringing peopletogether in one activity, namely the Rebo tradition activity Wekasan.Key Words: Study, Moral Values, Tradition, Rebo Wekasan.